DAMPAK PEMBANGUNAN PESISIR PANTAI TERHADAP KONDISI SOSIAL EKONOMI MASYARAKAT NELAYAN DI KELURAHAN MUARAREJA KECAMATAN TEGAL BARAT KOTA TEGAL - Muhamad Rijal Pamungkas (INUMIYA: Jurnal Ekonomi Pembangunan, 2023)
This research aims to find out the impact of coastal development on the socio-economic conditions of fishing communities in Muarareja Village, West Tegal District, Tegal City. This research produces findings that coastal development activities have an impact on changes in the socio-economic conditions of fishing communities, including: Coastal development encourages an increase in the income of the Muarareja fishing community, which is generally below the poverty line. This condition has implications for socio-economic changes in fishing communities for the better, improving housing conditions, improving public health conditions, environmental cleanliness, marine product production and distribution network systems, opening up fishing business opportunities, as well as modernization of the fishing system. Obstacles for fishermen in improving their economic level are low levels of education and training, lack of production equipment, profit sharing systems, as well as marketing factors and fish prices. Marketing factors in this location can be relatively resolved with good transportation routes, many fish drying businesses, and the use of small fish as shrimp feed.